ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS BANK SYARIAH DI INDONESIA - Ramadhan, Muhammad Rizky; Widiyanti, Dwi Retno (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This study aims to examine the effect of Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), Operating Cost divided by Operating Income (BOPO), and Non Performing Financing (NPF) to profitability proxied by Return on Assets (ROA) at Sharia Commercial Bank in the period of 2017-2021. The data used in the research was obtained from financial report data. This study population is the Sharia Commercial Banks. The sample selection technique used was purposive sampling and obtained 8 Sharia Commercial Bank with research period of 2017-2021 quarterly. The method of analysis in this research is the panel data regression using the Stata 17 software. The results shows that all independent variables (CAR, FDR, BOPO, NPF) affect the dependent variable profitability proxied by (ROA). Partially, it was found that CAR positively and significantly affects ROA, while FDR negatively and significantly affects ROA. Similarly, BOPO has a significant negative impact on ROA, as does NPF, which also has a significant negative impact on ROA.